A conceptual analysis of subjective health status in frail elderly Korean men - Eun Jeong Nam; Sun Jung Park (Journal of Men's Health)
This study seeks to define and examine the concept of subjective health status among the frail elderly Korean men. Using the concept analysis framework by Walker and Avant, 10 articles related to the subjective health status of frail elderly adults were selected for this study. The results of this study indicate that the antecedents are “State of vulnerable health among the seniors aged 65 or elderly” and “Elderly themselves are aware of their current health conditions”. The attributes are “Health promotional behavior”, “Efforts to maintain physical, mental and social well-being” and “Striving to achieve health goals”. The consequences are confirmed as “State where no complications occur” and “Improvement of life satisfaction”. This study is significant in that it clarifies the concept and attributes of frail elderly, reflecting the characteristics and objectives of nursing.